Seroprevalence of Leishmania spp., in dogs at Durán, Guayas province, Ecuador - Mendoza Castañeda, Georgia Elena; Macías Litardo, María Fernanda; Granoble Pincay, Mercedes Johanna (ECOAgropecuaria. Revista Científica Ecológica Agropecuaria, 2023)
Currently, zoonotic diseases must be constantly studied to identify the presence of vectors and establish possible endemic areas. In the present study, the presence of Leishmania spp. was determined in dogs from Durán canton, Guayas province, Ecuador, by means of the immunochromatographic test Bionote Leishmania Antibody. The research used a quantitative approach, with a descriptive, cross-sectional, non-experimental research design. Using the non-probabilistic sampling method by convenience. The population to be studied was 30 dogs selected from two sectors of the Durán canton. The results show one positive case, establishing a 3 % seroprevalence to identify Leishmania spp., Finally, the only positive case was an adult animal that had been outside for a longer period of time, establishing a low prevalence of leishmaniasis in the area.
Keywords: Epidemiology; cutaneous leishmania; visceral leishmania; vectors; zoonosis